Autism and obstacles in the labor market in a large city (Research, Society and Development, 2022)
Objective: To identify the main difficulties in the insertion of people with Autism Spectrum Disorder (ASD) in the professional process, as well as to evaluate their knowledge about Law 8.213/91, which regulates their rights in relation to work. Methodology: This is a cross-sectional, descriptive, quantitative-qualitative study, conducted in a training association for the labor market for people with ASD (n=22), in the year 2022, in Salvador, Bahia. The collection instrument was a semi-structured questionnaire, which included questions about the sociodemographic profile and barriers to entering the market. Results: Of the total, 36.36% stated that they are already part of the job, however, they evaluated their job performance as reasonable (87.50%) and reported that they cannot do all the activities that are delegated (100%). Asked about the Law, 68.18% answered that they are not aware and that they have already suffered some kind of prejudice or discrimination just because they are autistic (87.50%). Another feeling reported by 75% is that they feel excluded by their colleagues. In addition, they pointed out that the main difficulty in getting a job is the lack of preparation (54.55%). Conclusions: The biggest difficulties for entering the job market were performing delegated activities and prejudice or discrimination. In addition, ignorance of their rights under the law.